Characteristics of Unruptured Compared to Ruptured Intracranial Aneurysms: A Multicenter Case–Control Study. Issue 1 (25th July 2017) - Hostettler, Isabel C; Alg, Varinder S; Shahi, Nichole; Jichi, Fatima; Bonner, Stephen; Walsh, Daniel; Bulters, Diederik; Kitchen, Neil; Brown, Martin M; Houlden, Henry; Grieve, Joan; Werring, David J; et al.
Abstract: BACKGROUND: Only a minority of intracranial aneurysms rupture to cause subarachnoid hemorrhage. OBJECTIVE: To test the hypothesis that unruptured aneurysms have different characteristics and risk factor profiles compared to ruptured aneurysms. METHODS: We recruited patients with unruptured aneurysms or aneurysmal subarachnoid hemorrhages at 22 UK hospitals between 2011 and 2014. Demographic, clinical, and imaging data were collected using standardized case report forms. We compared risk factors using multivariable logistic regression. RESULTS: A total of 2334 patients (1729 with aneurysmal subarachnoid hemorrhage, 605 with unruptured aneurysms) were included (mean age 54.22 yr). In multivariable analyses, the following variables were independently associated with rupture status: black ethnicity (odds ratio [OR] 2.42; 95% confidence interval [CI] 1.29-4.56, compared to white) and aneurysm location (anterior cerebral artery/anterior communicating artery [OR 3.21; 95% CI 2.34-4.40], posterior communicating artery [OR 3.92; 95% CI 2.67-5.74], or posterior circulation [OR 3.12; 95% CI 2.08-4.70], compared to middle cerebral artery). The following variables were inversely associated with rupture status: antihypertensive medication (OR 0.65; 95% CI 0.49-0.84), hypercholesterolemia (0.64 OR; 95% CI 0.48-0.85), aspirin use (OR 0.28; 95% CI 0.20-0.40), internal carotid artery location (OR 0.53; 95% CI 0.38-0.75), and aneurysm size (per mm increase; OR 0.76; 95% CI 0.69-0.84). CONCLUSION: We show substantial differences in patient and aneurysm characteristics between ruptured and unruptured aneurysms. These findings support the hypothesis that different pathological mechanisms are involved in the formation of ruptured aneurysms and incidentally detected unruptured aneurysms. The potential protective effect of aspirin might justify randomized prevention trials in patients with unruptured aneurysms.